A study on the survival time, sex, weight and blood content of the Ehrlich Ascites Carcinoma involved tumour - Vennapusa, Nagarjuna Reddy; P. K. M, Nagarathna; M., Divya (International Journal of Pharmacological Research, 2013)
Experimental tumours have great importance in modelling, and Ehrlich ascites carcinoma (EAC) is one of the commonest tumours. EAC is referred to as an undifferentiated carcinoma and is originally hyperdiploid, has high transplantable capability, no-regression, rapid proliferation, shorter life span, 100% malignancy and also does not have tumour-specific transplantation antigen (TSTA). EAC resembles human tumours which are the most sensitive to chemotherapy due to the fact that they are undifferentiated and that they have a rapid growth rate. The ideal drug being ineffective or minimally effective for normal cells have been focused on, and at this point, the usage of natural sources as an alternative cancer therapy is thought to have a great value for cancer control and programs destructio n.